Using ONIOM calculations to investigate the abilities of simple and nitrogen, boron, sulfur‐doped carbon nanotubes in sensing of carbon monoxide. Issue 12 (14th March 2020) - Tavakol, Hossein; Hassani, Fahimeh; Shahabi, Dana
Abstract: In this work, geometries, stabilities, and electronic properties of the carbon monoxide (CO) molecule as an adsorbent in a simple carbon nanotube (CNT) and nitrogen (N), boron (B), sulfur (S)‐doped CNTs (NCNT, BCNT, and SCNT) with parallel and perpendicular configurations are fully considered using ONIOM, natural bond orbital, and quantum theory of atom in molecule (QTAIM) calculations. The adsorption energies ( E ad ) demonstrate that a CO molecule could be adsorbed on the surface of the simple CNT with parallel configuration and N‐doped CNT with perpendicular configuration in an exothermic process. QTAIM calculations showed the close‐shell (noncovalent) interactions between the CO molecule and CNT or N, B, S‐doped CNTs. In addition, the energy gap ( E g ) values between the highest occupied molecular orbital and the lowest unoccupied molecular orbital are calculated. In accordance with the results of energy gap, simple and N‐doped CNTs could be used as CO sensors. Abstract : ONIOM calculations are used to examine CO sensing by various simple and doped (with N, B, and S) single‐walled carbon nanotubes (CNTs). The adsorption energies and sensor properties are investigated using density functional theory, natural bond orbital, and quantum theory of atoms in molecule calculations. Among the studied structures, N‐doped CNTs have the highest abilities, and the reliability of ONIOM calculations for this process is confirmed.